European experience of implementing eco-innovations as part of the general strategy of the company's development (Economics and region, 2023)
The article examines the essence and significance of eco-innovations for Ukraine in 2023. Their varieties (technical, social and institutional eco-innovations) are also characterized with the aim of their further successful implementation and use in various spheres of activity. The main reason for the relevance of this issue was the damage caused to the environment as a result of the destructive influence of the military actions of the aggressor country, therefore there is an urgent need to green the production facilities of enterprises. The food industry suffered great losses, for example, the production of food products, beverages and tobacco products disappeared completely or decreased. In the Kyiv region alone, a fifth of warehouse space was lost, which is about 364,000 square meters, including office space and other buildings on the territory of the complexes. For these reasons, the level of availability of eco-innovations in foreign countries, such as: France, Germany, the Czech Republic for the period 2013-2022, and their structural component indicators (material and water productivity, employment in the field of environmental protection, management resources and certification). The elements of the Global Innovation Index (GII) and the dynamics of its development in Ukraine for the period 2018-2022 were studied. Environmental innovations are considered and analyzed on the example of the improvement of the own packaging of the American multinational company Mondelez international in the Czech Republic to overcome the consequences of economic crisis processes. Recommendations were given to Ukrainian enterprises to improve the environmental situation in production, such as: using the technology of using fallen leaves and recycled fiber for paper production from the Releaf company, participating in the educational grant program "Social Innovations of Communities" and on crowdfunding platforms (My City, Spilnokosht, KUB, Na-Starte, Kickstarter), attracting foreign grant programs, venture capital (AVentures Capital, Noosphere Venture Partners funds) and bank loans related to the financing of innovative activities of Ukrainian enterprises.
Keywords: innovations; eco-innovations; greening of production; foreign experience; innovation strategy; investments